2020
DOI: 10.1155/2020/8165296
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Acupoints in Treating Patients with Chronic Obstructive Pulmonary Disease: An Apriori Algorithm‐Based Association Rule Analysis

Abstract: Chronic obstructive pulmonary disease (COPD) is highly prevalent and a major burden on the healthcare system worldwide. It has a severe impact on patients due to poor health-related quality of life (HRQL), dyspnea, and exertional intolerance. Our previous meta-analysis revealed that body acupuncture therapy had adjuvant benefits of improving HRQL in COPD patients undergoing optimal medical treatment. Previous studies indicated that treatment with combinations of acupoints was more effective than single acupoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 17 publications
(31 reference statements)
0
29
0
1
Order By: Relevance
“…High-frequency electrical stimulation of ST36 in diabetic rats can promote the regeneration of lost enteric neurons through glial cell-derived neurotrophic factor and phosphatidylinositol-3 kinase/Akt signaling pathways [38]. e combination of acupoints was reported to exhibit greater therapeutic efficacy than a single acupoint [39,40]. Wang et al reported that the combination of multiple acupoints resulted in improved the score of the Pittsburgh sleep quality index and Athens Insomnia Scale via regulation of the activity of the brain area related to sleep experience [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-frequency electrical stimulation of ST36 in diabetic rats can promote the regeneration of lost enteric neurons through glial cell-derived neurotrophic factor and phosphatidylinositol-3 kinase/Akt signaling pathways [38]. e combination of acupoints was reported to exhibit greater therapeutic efficacy than a single acupoint [39,40]. Wang et al reported that the combination of multiple acupoints resulted in improved the score of the Pittsburgh sleep quality index and Athens Insomnia Scale via regulation of the activity of the brain area related to sleep experience [39].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of acupoints was reported to exhibit greater therapeutic efficacy than a single acupoint [ 39 , 40 ]. Wang et al reported that the combination of multiple acupoints resulted in improved the score of the Pittsburgh sleep quality index and Athens Insomnia Scale via regulation of the activity of the brain area related to sleep experience [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mathematically, support was the fraction of the total number of transactions in which the itemset occurred, measuring the statistical significance of association rules in the whole dataset. Confidence was the conditional probability of the occurrence of consequent, given the antecedent, reflecting the credibility degree of association rules [18]. In brief, the support of A ⟶ B indicated that the prescriptions containing both acupoint A and acupoint B account for the total ones; and the confidence of A ⟶ B displayed that the prescriptions containing both acupoint A and acupoint B account for the ones containing acupoint A.…”
Section: Data Processingmentioning
confidence: 99%
“…The questionnaire comprised two sections: the self-made general information and prevalence of chronic [21]. Based on this study, the support of A→B was the probability of the simultaneous occurrence of chronic disease A and B.…”
Section: Instrumentsmentioning
confidence: 99%